Kapabilitas sumber daya transformasi industri 4.0 dan pengaruhnya terhadap industri mikro kuliner berkelanjutan dan ekonomi sirkular kawasan metropolitan - Qanita, Aisyah; Rafif Alhakim, Muhammad; Kamila Hanum, Rastinia; Gita Anggraeni, Deby (Institute for Advanced Science Social, and Sustainable Future, 2024)
Industrial Revolution 4.0 (I4.0) is a major trend in various sectors, including IMK, which is very important in Indonesia. I4.0 supports sustainable development and sustainable business while minimizing environmental impact. This study aims to identify key resources for the adoption of Industry 4.0 and its impact on the sustainable business and circular economy of the Jakarta culinary IMK. This study uses mixed methods (mixed methodology) with exploratory analysis (Explanatory Factor Analysis/EFA) and modeling-based hypothesis testing. The initial stage involved a PRISMA-based systematic literature review (SLR) to form a theoretical model. Model testing uses structural equation modeling with partial least squares (SEM PLS). Data was obtained from field questionnaires given to 293 culinary micro- and small-industry (IMK) players in the Jakarta metropolitan area. The research results found that production system management, HR leadership, and green business operations influence the adoption of I4.0 and sustainable culinary production systems. The use of information technology as an important key also supports the adoption of Industry 4.0 and the sustainable production system of Jakarta metropolitan culinary IMK. In the end, both the adoption of Industry 4.0 and sustainable culinary production systems have a significant impact on circular economy capabilities and sustainable business. This study provides recommendations for local governments to facilitate technology adoption, provide financial support, and have adequate IT infrastructure. The government can also start integrating sustainable circularity rules into the requirements for IMK Culinary to enter the consumer goods procurement market on the government's agenda. The IMK Association can promote collaboration and education, as well as advocacy for circular IMK business. Academics can provide training and innovation research related to technology adoption and sustainable practices at culinary IMKs in Jakarta.